IMPLEMENTASI CYBER PUBLIC RELATIONS PT JASAMARGA TRANSJAWA TOL REPRESENTATIVE OFFICE 2 CIREBON DALAM MENINGKATKAN KESADARAN BERKENDARA AMAN MELALUI MEDIA SOSIAL INSTAGRAM @official.jmpalikanci - Devi Wulandari; Ririn Risnawati; Nurul Chamidah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
This study aims to understand how the cyber public relations (CPR) process is carried out by PT Jasamarga Transjawa Tol Representative Office 2 Cirebon in conveying information about driving safety through social media Instagram @official.jmpalikanci. The background of this study arose from the risk of traffic accidents on the Palikanci toll road which were mostly caused by road user negligence and lack of understanding about safety, such as drowsiness while driving, high speed, and flat tires. Therefore, the company's public relations unit conveys information to the public digitally by utilizing Instagram as a fast, broad, and interactive two way communication media. This study uses a qualitative approach with data collection techniques through participatory observation, semi-structured interviews, and visual documentation related to the delivery of driving safety messages. Data analysis was carried out based on the public relations process framework according to Cutlip, Center, and Broom (2016) which consists of four main stages, namely defining the problem; planning and programming; taking action and communicating; evaluating the program. The communication process is carried out through collaboration between public relations, operations, and IT (Information Technology) teams, with the preparation of information in the form of short videos (reels) and e flyers that are adjusted to the characteristics of Instagram users. Information is published routinely and uses a persuasive, communicative, and visual language style. Evaluation is carried out internally through accident data and Instagram's insight features. Meanwhile, external evaluation is carried out by the PT Jasamarga head office through an annual survey. However, at the time of the study, external evaluation had not been carried out in the RO 2 Cirebon area. Based on the results of the study, it shows that the cyber public relations (CPR) process carried out by PT Jasamarga Transjawa Tol Representative Office 2 Cirebon is carried out in a structured and consistent manner, using Instagram social media as a medium for delivering educational information visually, while also providing a space for interaction between agencies and the public that can contribute to increasing awareness. Through the implementation of a structured public relations process, safety information can support increasing driving awareness among toll road users.